Exploring the support needs of newly appointed departmental heads: A South African perspective - Michael Moreti Mahome; Lydia Kgomotso Mphahlele (International Journal of Educational Management and Development Studies)
Numerous middle leadership researchers in education worldwide have conceded the value and the contribution of Departmental Heads (DHs) in enhancing the achievement of the learners. Yet researches generate insufficient insights on this topic work and on how middle leaders can be supported. Hence, this study deals with the exploration of support needs of newly appointed DHs in three South African secondary schools in District No. 10 (D10) in the province of Gauteng. There is a dearth in literature worldwide on the support needs of newly appointed DHs, more especially in the South African milieu. Lodged within Schlossberg’s theory of transition, this phenomenological qualitative study intends to support newly appointed DHs as a point of focus to close the existing gap in knowledge of their support needs. A case study design was chosen where in-depth one-on-one interviews were conducted with nine purposively selected DHs from three schools. Wellington’s seven-stage thematic analysis data model was used to analyse data, with the support of Quirkos. The findings indicated that DHs need suitable support in a form of induction that incorporates orientation and mentoring to perform their role. For this, this study suggests that the ministry of basic education take all the newly appointed DHs thorough an induction programme before assuming their role to enable them to effectively lead and manage teaching staff and educational processes. The findings will reshape how the Department of Basic Education view the professional development of DHs.